Local Instruction Theory Linear Inequality of One Variable Based on RME to Cultivate Students’ Mathematical Communication - Iryana Muhammad; Al Jupri; Kusnandi; Siti Fatimah (RANGE: Jurnal Pendidikan Matematika, 2026)
Mathematical communication is a fundamental competency that allows students to interpret, represent, and convey mathematical ideas effectively. This study aims to examine the achievement of students' mathematical communication skills through the application of Local Instructional Theory (LIT) to one-variable linear inequality material within the framework of Realistic Mathematics Education (RME). The research uses a design research approach carried out through two teaching experiments, namely TE-1 with 31 students and TE-2 with 26 students at one of the junior high schools in Lhokseumawe. The results showed a significant increase from TE-1 to TE-2 in three indicators of mathematical communication ability, namely: (1) describing graphs into mathematical sentences (58% → 77%); (2) describe or explain mathematical ideas in writing (45% → 96%); and (3) expressing the situation into mathematical language or symbols and developing a solution strategy (39% → 77%). This increase is influenced by the revision of the learning design, which is carried out cyclically and reflectively, so that students better understand the context of the problem, can reflect on the thinking process, and convey solutions mathematically. These findings provide the implication that LIT-based learning design with an RME approach can be a practical reference for teachers and curriculum developers in designing learning activities that systematically and contextually encourage students' mathematical communication skills. This research also affirms the potential of design research in developing local instructional theories that bridge theoretical insights with classroom learning practices.